The chondrocytic journey in endochondral bone growth and skeletal dysplasia. Issue 1 (27th March 2014) - Tsang, Kwok Yeung; Tsang, Shun Wa; Chan, Danny; Cheah, Kathryn S.E.
Abstract : The endochondral bones of the skeleton develop from a cartilage template and grow via a process involving a cascade of chondrocyte differentiation steps culminating in formation of a growth plate and the replacement of cartilage by bone. This process of endochondral ossification, driven by the generation of chondrocytes and their subsequent proliferation, differentiation, and production of extracellular matrix constitute a journey, deviation from which inevitably disrupts bone growth and development, and is the basis of human skeletal dysplasias with a wide range of phenotypic severity, from perinatal lethality to progressively deforming. This highly coordinated journey of chondrocyte specification and fate determination is controlled by a myriad of intrinsic and extrinsic factors. SOX9 is the master transcription factor that, in concert with varying partners along the way, directs the different phases of the journey from mesenchymal condensation, chondrogenesis, differentiation, proliferation, and maturation. Extracellular signals, including bone morphogenetic proteins, wingless‐related MMTV integration site (WNT), fibroblast growth factor, Indian hedgehog, and parathyroid hormone‐related peptide, are all indispensable for growth plate chondrocytes to align and organize into the appropriate columnar architecture and controls their maturation and transition to hypertrophy. Chondrocyte hypertrophy, marked by dramatic volume increase in phases, is controlled by transcription factors SOX9, Runt‐related transcription factor, and FOXA2. Hypertrophic chondrocytes mediate the cartilage to bone transition and concomitantly face a live‐or‐die situation, a subject of much debate. We review recent insights into the coordination of the phases of the chondrocyte journey, and highlight the need for a systems level understanding of the regulatory networks that will facilitate the development of therapeutic approaches for skeletal dysplasia. Birth Defects Research (Part C) 102:52–73, 2014. © 2014 Wiley Periodicals, Inc.